L’évolution de l’assurance de dommages au Canada et le positionnement de Sodarcan - Parizeau, Robert (Assurances, 1991)
The author first examines the property & casualty insurance market in 1990 and the economic role of property & casualty insurance in the context of the deregulation of financial institutions, compared with the banking system. He then provides a summary of the industry's view on employment, capitalization, revenues and the role played by foreign companies. Mr. Parizeau goes on to identify the position of Sodarcan inc., which, through a group of professional autonomous subsidiaries, operates in four specialized sectors: insurance brokerage, actuarial services and employee benefits, reinsurance brokerage and reinsurance underwriting. He concludes with a close examination of a number of issues that are shaping Sodarcan's business environment.